Hierarchical processing in Balint’s syndrome: a failure of flexible top-down attention - Mevorach, Carmel; Shalev, Lilach; Green, Robin J.; Chechlacz, Magdalena; Riddoch, Jane; Humphreys, Glyn W. (Frontiers in Human Neuroscience, 2014)
Patients with Balint's syndrome are typically impaired at perceiving multiple objects simultaneously, and at evaluating the relationship between multiple objects in a scene (simultanagnosia). These deficits may not only be observed in complex scenes, but also when local elements of individual objects must be integrated into a perceptual global whole. Thus, unlike normal observers, patients with simultanagnosia typically show a bias towards the local forms, even to the extent that they cannot identify the global stimuli. However, we have previously shown that global processing is still attainable in Balint patients in certain scenarios (e.g., when local elements are unfamiliar). This suggests that in addition to a possible perceptual deficit that favors the local elements in these patients, impaired attentional control may be at the core of their unique performance. To test this hypothesis we manipulated the perceptual saliency of the local and global elements in a compound letter task so that it included global-more-salient or local-more-salient displays. We show that a Balint patient was able to accurately identify both global and local targets as long as they were the salient aspect of the compound letter. However, substantial impairment was evident when either the global or local elements were the less salient aspect of the compound letter. We conclude that in Balint’s syndrome there is a failure of flexible top-down attention both in biasing attention away from salient irrelevant aspects of the display (salience-based-selection) and in impaired disengagement from irrelevant but salient items once they have been selected.